Pengaruh Fermentasi Limbah Cair Pulp Kakao terhadap Tingkat Keracunan dan Pertumbuhan Beberapa Gulma Berdaun Lebar - Pujisiswanto, Hidayat (Politeknik Negeri Lampung., 2012)
The research was conducted to determine the effect of fermentation liquid waste cocoa pulp on the level of toxicity and growth some broad-leaved weeds. Experiments conducted in Way Halim, Sukarame, Bandar Lampung. The timing of the trial starting from June to July 2011. The design used was Randomized Design Group (RAK) with one factor, namely the time of fermentation of cocoa pulp effluent, namely: 1 week, 2 weeks, and 3 weeks. Each treatment was repeated thrice. Weed seeds used are young or vegetative phase. The results showed: (1) The Liquid waste cocoa pulp on the fermentation 2 and 3 weeks are able to control the growth of broad leaf weeds up to 4 MSA, visible from suppression the dry weight of weeds and levels of toxicity. (2) Fermentation 1-3 weeks to control weed growth Cleome rutidospermae DC and Agerotum conyzoides, while the other weeds that can be controlled with Asystasia gangética fermentation 3 weeks and Synedrella nudiflora able to be controlled by the fermentation of 2 and 3 weeks up to 4 MSA (3) Toxicity caused by the fermentation of cocoa pulp liquid waste is contact to visible blotches and burning weeds on the affected part. Keywords: broadleaf weeds, cocoa pulp, fermentation